Maternal Thyroid Dysfunction and Neonatal Thyroid Problems - BEREKET, ABDULLAH; ÖZEK, EREN; BİLGEN, HÜLYA SELVA; ÖZDEMİR, HÜLYA; DEMİRCİOĞLU, SERAP (HINDAWI LTD, 2013)
Aim. To investigate obstetric features of pregnant women with thyroid disorders and thyroid function tests of their newborn infants. Methods. Women with hypothyroidism and having anti-thyroglobulin (ATG) and anti-thyroid peroxidase (anti-TPO) antibodies were assigned as group I, women with hypothyroidism who did not have autoantibodies were assigned as group II, and women without thyroid problems were assigned as group III. Results. Pregnant women with autoimmune hypothyroidism (group I) had more preterm delivery and their babies needed more frequent neonatal intensive care unit (NICU) admission. In group I, one infant was diagnosed with compensated hypothyroidism and one infant had transient hyperthyrotropinemia. Five infants (23.8%) in group II had thyroid-stimulating hormone (TSH) levels >20 mIU/mL. Only two of them had TSH level >7 mIU/L at the 3rd postnatal week, and all had normal free T4 (FT4). Median maternal TSH level of these five infants with TSH >20 mIU/mL was 6.6 mIU/mL. In group III, six infants (6.5%) had TSH levels above >20 mIU/mL at the 1st postnatal week. Conclusion. Infants of mothers with thyroid problems are more likely to have elevated TSH and higher recall rate on neonatal thyroid screening. Women with thyroid disorders and their newborn infants should be followed closely for both obstetrical problems and for thyroid dysfunction.
Keywords: TRANSIENT CONGENITAL HYPOTHYROIDISM; EARLY-PREGNANCY; SUBCLINICAL HYPOTHYROIDISM; HORMONE PARAMETERS; CONSEQUENCES; ANTIBODIES; MANAGEMENT; GESTATION; INFANT; WOMEN